Penyelesaian Wanprestasi Perjanjian Franchise : (Studi Kasus Franchise Tentang Kita Cokelat Di Lombok) - M. Ramadoni Ali Saputro; Eka Jaya Subadi (Fakultas Hukum Universitas Mataram, 2023)
This research purposed to find out the cause of contact breaching by the franchisee Tentang Kita Chocolate and to find out the settlement of the case by the franchisee Tentang Kita Chocolate. The method used within this study is an empirical normative legal research method. Based on the results of the research, it is known that the franchise agreement of Tentang Kita Chocolate is in accordance with the Civil Code, but is said to be lacking when viewed from Government Regulation Number 42 of 2007 Concerning Franchise. The franchisor does not carry out any of its obligations, but for legal consequences if the obligations are not carried out by the parties are not regulated in the agreement, if losses arise in the future due to these reasons, it will be resolved by way of deliberation in accordance with the contents of the agreement.